UNVEILING THE NEXUS OF SELF-CONFIDENCE AND LEARNING DISCIPLINE ON ECONOMICS STUDENTS' ACADEMIC ACHIEVEMENT - Ramadhanti, Fenty; Wibowo, Agus; Febriantina, Susan (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This research aims to determine the influence of self-confidence and learning discipline on the learning achievement of students at the Faculty of Economics, Jakarta State University. The research used in this research is a causal quantitative method. The population in this study was 968 students from the Faculty of Economics, Universitas Negeri Jakarta, class of 2021. The technique for determining the sample in this study used a purposive proportional random sampling technique so that the sample in this study was 242 students. The results of the analysis using Partial Least Square (PLS) show that self-confidence has a positive and significant effect on learning achievement. Learning discipline shows positive and significant results on learning achievement. Self-confidence has a positive and significant effect on learning discipline. Self-confidence through learning discipline has a positive and significant effect on learning achievement.